From Peruvian Guano to Electronic Records: Canadian E-Discovery and Records Professionals - Force, Donald C. (Archivaria, 2010)
The exponential growth of electronic records has led archivists and records managers to develop ever more sophisticated approaches to manage and preserve these records, not only to support an organization’s daily operations but to alleviate the records retrieval burden in the event that the organization encounters litigation. The electronic discovery process has added additional pressure to the responsibilities of records professionals by holding organizations accountable for the documentation they disclose as well as that which they cannot produce. In North America, American court rulings on e-discovery issues have largely overshadowed those in Canada. This article provides a historical perspective of the emergence of e-discovery in Canada, and discusses the relationship records professionals have with numerous Canadian judicial decisions and the discovery process. RÉSUMÉ L’augmentation exponentielle des documents numériques a mené les archivistes et les gestionnaires de documents à développer des approches de plus en plus sophistiquées pour gérer et conserver ces documents, non seulement pour appuyer les opérations quotidiennes d’une organisation, mais aussi pour faciliter le repérage de ces documents dans l’éventualité d’un procès. Le processus d’administration de la preuve électronique a ajouté des nouvelles pressions aux responsabilités des professionnels de l’information, puisque les organisations sont tenues responsables des documents qu’elles rendent disponibles aussi bien que de ceux qu’elles ne peuvent pas fournir. En Amérique du Nord, les décisions des tribunaux américains par rapport aux questions de l’administration de la preuve électronique ont grandement éclipsé celles des tribunaux canadiens. Cet article fournit une perspective historique de l’émergence de l’administration de la preuve électronique au Canada et commente des liens entre les professionnels de l’information et les nombreuses décisions judiciaires canadiennes, de même qu’avec le processus d’administration de la preuve électronique.